2001
DOI: 10.1089/089277901753205753
|View full text |Cite
|
Sign up to set email alerts
|

Supracostal Approach in Percutaneous Nephrolithotomy: Experience with 102 Cases

Abstract: Supracostal puncture in a safe and effective approach with acceptable morbidity in selected cases of staghorn, upper ureteral, and upper caliceal calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 9 publications
6
32
0
1
Order By: Relevance
“…But in our study complication rate is low and patient can be managed symptomatically. (Kekre et al, 2001) Bjurlin et al in his study of 214 patients with 21 % intercostals access found chest x-ray routinely as unnecessary practice. Low complication rates of procedure along with symptomatology can displace routine chest x ray.…”
Section: Resultsmentioning
confidence: 98%
“…But in our study complication rate is low and patient can be managed symptomatically. (Kekre et al, 2001) Bjurlin et al in his study of 214 patients with 21 % intercostals access found chest x-ray routinely as unnecessary practice. Low complication rates of procedure along with symptomatology can displace routine chest x ray.…”
Section: Resultsmentioning
confidence: 98%
“…Yüz iki, 1350, 240 olguluk faklı serilerde suprakostal PNL girişimlerinde intratorasik komplikasyon oranları sırasıyla; %10, %20, %1,8 olarak bildirilmiş ve suprakostal girişimlerde subkostal girişime göre daha fazla yan etki oranı belirtilmiştir (11)(12)(13). Yazkan ve ark.…”
Section: Discussionunclassified
“…Overall, the occurrence of pulmonary complications in our series was comparable with prior series. [2][3][4][5][6][7] Using a working sheath of adequate size during PCNL via the supracostal approach may prevent pleural complications. We believe that it is important to keep a low pressure within the irrigation system during PCNL to minimize the possibility of fluid entering the pleural space.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the superior calyceal approach in percutaneous renal surgery has been reported by many authors. [2][3][4][5][6][7] However, it is usually a concern because of the potential complications of pneumothorax, hydrothorax, pleural effusion, and lung injury.…”
mentioning
confidence: 99%